Значение водяной растительности в выхухолевых угодьях Европейской части СССР - Самарин, В.Ф. (Вестник зоологии, 1975)
Ecological conditions of desman lands were studied for 1971-1972 in the territory of the Voroshilovgrad state reservation of the Ukrainian Academy of Sciences. With the same aim the areas in the high-water beds of the rivers Kotoros! (the Yaroslavl Region), Oka (the Murom district, the Vladimir Region), Bityung and Khoper (the Voronezh Region) most densely inhabited by desman were also examined in the autumn of 1972. A definite relation was found between the degree of the water bodies overgrowing by vegetation and density of desman in them.